Characterization of polyhydroxybutyrate biosynthesized from crude glycerol waste using mixed microbial consortia. Issue 3 (3rd December 2012) - Hu, Shengjun; McDonald, Armando Gabriel; Coats, Erik Robert
Abstract This study focused on the characterization of polyhydroxybutyrate (PHB) produced from crude glycerol (CG) using mixed microbial consortia (MMC). PHB recovered from two biomass drying treatments (65°C oven drying and lyophilization) was characterized comparatively along with a commercially sourced PHB (PHB‐C). Characterization results showed that oven‐drying method caused PHB partial hydrolysis, as indicated by its lower molecular weight (Mw) (PHB‐O, 144, 000 g mol−1), which further affected its physical and chemical properties. Lyophilization helped alleviate PHB hydrolysis during drying process, leading to PHB (PHB‐L) of higher Mw (309, 000 g mol−1) and material properties comparable with commercial PHB. Furthermore, crystallization and morphological studies showed that PHB‐L featured faster crystallization rates and smaller spherulites as compared with PHB‐C, probably due to its lower Mw. In general, the results from this study suggested that CG‐MMC‐derived PHB‐L possessed material properties comparable with those of pure substrate/culture produced PHB. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013